Laparoscopic treatment of adrenal masses in children: Report of two cases and review of literature - Antonio Orofino; Cosetta Maggipinto; MariaPaola Lanzillotto; Michele D'Amato; Massimo Ronzini; Guglielmo Paradies (Wolters Kluwer Medknow Publications, 2016)
Laparoscopic adrenalectomy has become a common alternative to open surgery for the resection of adrenal lesions in adults: The advantages are to provide better exposure of the adrenal gland, diminish soft tissue dissection, decrease morbidity and postoperative pain; however, reporting on the laparoscopic adrenalectomy in paediatric patients has been limited. We present two cases of laparoscopic adrenalectomy performed at our institution in two children, for left adrenal neuroblastoma in a first patient with opsomyoclonus syndrome, and for a right incidentaloma in the second case. According to recent literature, our experience has demonstrated that the laparoscopic adrenalectomy is a feasible procedure in children with small, well-circumscribed adrenal masses: It can be used a safety to treat suspected benign and malignant adrenal masses in children, with minimal morbidity and short hospital stay. The lateral trans-peritoneal approach offers optimal visualisation and good outcomes in terms of minimal discomfort, rapid recovery and excellent cosmesis. However, in the paediatric field, the number of patients is limited, making the learning curve longer.